Association of micropapillary urothelial carcinoma of the bladder and BK viruria in kidney transplant recipients. Issue 3 (1st April 2013) - Bialasiewicz, S.; Cho, Y.; Rockett, R.; Preston, J.; Wood, S.; Fleming, S.; Shepherd, B.; Barraclough, K.; Sloots, T.P.; Isbel, N.
Abstract: Introduction: BK virus (BKV) is an ubiquitous human polyomavirus that establishes latency in urothelium. BKV is known to re‐activate in immunosuppressed individuals, and is an increasingly important cause of nephropathy and graft loss in kidney transplant recipients. Animal studies have demonstrated BKV has a potential role as a tumor virus. However, its role in precipitating or facilitating oncogenesis in humans is still debated. Report: We report 2 cases of aggressive micropapillary urothelial carcinoma of the bladder in kidney transplant recipients with persistent BK viruria and preserved graft function. Results: In both cases, polyomavirus immunohistochemistry performed on the tumor specimens was strongly positive, and limited to the malignant tissue. BKV DNA, viral protein 1, and large T antigen mRNA were detected in the tumor; however, no viral particles were seen on electron microscopy. Conclusion: In one of the cases, BKV integration into the host genome was identified, leading to the truncation of the major viral capsid gene. This finding raises the concern that persisting BK viruria may be a risk factor for this aggressive form of bladder cancer. Further studies to determine screening and management strategies are required.